STEAM in the Perspective of 21st Century Mathematics Learning: A Field Study of Indonesia and Malaysia - Aziz, Abdul; Iswahyudi Joko Suprayitno; Alma Rif’atun Nisa (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
The aim of this study is to explore the implementation of the STEAM approach in Indonesia and Malaysia in relation to mathematics learning concepts and the skills developed during the mathematics learning process. This study employs a descriptive qualitative method with school students as the research subjects, aiming to examine the application of STEAM in the learning process in both countries. The findings reveal that the integration of STEAM has a positive impact on mathematics learning, particularly in enhancing students’ confidence as well as their critical thinking, creativity, communication, and collaboration skills. The application of STEAM in the context of 21st-century mathematics education encourages students to build self-confidence in facing challenges, which is essential for maximizing their potential.